An analysis of classroom culture of BRAC schools - Imam, Syeda Rumnaz; Khan, Kaisar A (BRAC Research and Evaluation Division (RED), 2019)
This study aimed at examining the classroom culture of two types of BRAC schools, i.e., Non Formal Primary Education (NFPE) and Chandina Learning Improvement Project (CLIP). Two schools from each category were selected purposely, and each school was observed for a week. The NFPE schools are based mainly on large group method, according to which, the students are found to be seated in a large U shaped group and all the activities in the class are done within this group. On the other hand, CLIP schools are based mainly on small group method. The whole class is divided into five small groups, each containing 5-6 members and a group leader. Most of the classroom activities are done within these small groups in CLJP schools. Although the small group method has been implemented successfully in the educational processes in different countries, it does not seem to have been particularly successful in BRAC schools. Teacher's training and supervision of teachers skills need to be enhanced in order meet the goals set by a well-planned project like CLIP. The large group method seems to see more effective compared to the small group method. Some other drawbacks that were also found in the classroom practices in both types of schools were lack of adequate explanation of the lessons, pressure to recall lessons word by word, lack of pedagogical skills among the teachers, absence of the practice of asking questions to the teachers, some problems with the materials, gap in the process of supervision, and above all lack of gender sensitivity. The introduction of any innovative teaching method can not bring fruitful results unless the facilitators and the supervisors are trained enough to effective implementation. Thus, pedagogical skills of the teachers and supervision skills of the staff should be improved through effective training.